KOMPETENSI PEDAGOGIK MAHASISWA DALAM MENGELOLA PEMBELAJARAN TEMATIK INTEGRATIF KURIKULUM 2013 PADA PENGAJARAN MICRO DI PGSD UAD YOGYAKARTA - Indirani, Fitri (Profesi Pendidikan Dasar, 2015)
This study aims to determine; (1) The pedagogical competence of students in managing integratedthematic learning curriculum in 2013 on micro teaching; (2) determine the barriers faced by students inmanaging integrated thematic learning curriculum in 2013 on micro teaching. This type of research is afield research using qualitative approach. The results showed that; (1) The pedagogical competence ofstudents in managing integrated thematic learning curriculum in 2013 on micro teaching is good. It isshown from the four aspects of pedagogical competence. (2) the barriers faced by students in managingintegrated thematic learning curriculum teaching in 2013 at the micro, for example developingassessment instruments; linking indicators each subject according to the theme; removal of subjectsone to the other subjects; making educative media according to the theme; developing material.